Salinity gradient power using in the Black Sea regions (in frame of the blue growth development) - Slizhe, Mariia; Berlinsky, Nikolai; El Hadri, Youssef (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Problem Statement. Today, humanity is in search of new sources of energy to make the economy more sustainable, as well as the need for a transition to energy that works on the principles of Carbon-Free Technology. For the Black Sea, this is expressed in the desire for successful implementation of the program Blue Growth Accelerator, which is aimed at the introduction of innovative technologies and alternative energy sources in the energy sector of the Black Sea countries, for the development of the "Blue Economy" and the achievement of its healthy, productive and sustainable state. Salinity gradient power (SGP) is one of the new renewable energy sources. The most studied methods for obtaining SGP energy are technologies based on: Reverse Electrodialysis and Pressure Retarded Osmosis. The interaction of fresh and salt water can provide, in fact, unlimited, free and clean energy. The basis for the generation of such energy is the so-called salinity gradient that occurs when two types of water are mixed. After decades of work and numerous experiments, scientists have developed a way to use the energy of the salinity gradient to generate electricity. This type of electricity is also called "Blue Energy" by association with the color of mixing freshwater and salt water when rivers flow into the ocean. Places (estuaries or deltas), where rivers flow into the oceans and seas, have a truly enormous energy potential.The aim of this study is to identify sites in the northwestern Black Sea region with the necessary conditions for the development of Salinity Gradient Power energy, as well as to assess their potential using the example of estimating the maximum theoretical power of the Pressure Retarded Osmosis process.Research Methodology. In a PRO system, the less concentrated solution flows towards the more concentrated solution due to the positive osmotic pressure difference as long as this difference remains greater than the hydrostatic pressure difference. It is by this principle that osmotic power is produced. Theoretically available amount of energy released when mixing 1 m3 of saturated brine (5 mol/l NaCl solution) and 1 m3 of sea water (0.5 mol/l NaCl) at 293 K is 10 MJ. In the northwestern Black Sea region, along the coast between the Danube and Dnieper rivers, there are 21 limans (lagoons) of which some can be used to generate of Salinity Gradient Power.Results. The results of calculating the maximum net power showed that highest values obtained in the summer months, when the salinity in limans reaches its maximum and, consequently, its difference with the salinity of sea (river) water increases. Proceeding from maximum net power, obtained for the Western Sivash, where the salinity is maintained artificially at certain values, it can be seen that the annual amplitude has a smaller value, which provides more stable conditions. There are objects in the northwestern Black Sea region, in the waters of which, as soon as technologies become available, it will be possible to implement SGP projects. The Kuialnyk Liman, Sasyk- Sivash lake and Western Sivash have the most favorable conditions, where the highest power indicators are shown when using the sea water – hypersaline solution scheme, in which freshwater is not consumed.